The Validity of Hilal Sighting Testimony According to the Imams of the Madhhab: A Jurisprudential Study and Contemporary Issues - Muhammad Himmatur Riza; Ahmad Izzuddin; Restu Trisna Wardani (Universitas Islam Negeri Mataram, 2026)
The determination of the beginning of lunar months, particularly Ramadan, Shawwal, and Dhu al-Hijjah, is a crucial issue in the religious life of Muslims as it is directly related to the performance of worship. One of the critical aspects in this determination is the validity of testimony in the sighting of the new crescent moon (rukyatul hilal). This article aims to comprehensively examine the perspectives of the Islamic legal schools (imam mazahib) regarding the requirements, number, and admissibility of witnesses in rukyatul hilal, as well as to analyze their implications in a contemporary context. The research method employed is a library study with a comparative fiqh analysis approach, by comparing the opinions of the Hanafi, Maliki, Shafi‘i, and Hanbali schools based on classical fiqh literature and modern fatwas. The findings indicate that there are fundamental differences among the schools concerning the number of witnesses, the acceptance of individual testimony, and the criteria of witness credibility. These differences stem from distinct methodologies of legal reasoning (istinbat al-hukm) and approaches to interpreting hadith. Contemporary analysis emphasizes that such differences should be understood as part of the richness of Islamic jurisprudence, while also opening new avenues of ijtihad for the unification of the Hijri calendar in Indonesia. Thus, this study is expected to contribute to strengthening the discourse on hisab-rukyat fiqh in the modern era.